Розробка компонентів інформаційної системи супроводження спортивних заходів регіонального рівня - Кравченко, В. Д. (ХНУРЕ, 2024)
The main problem with regional sports events lies in the fact that many people do not know about them. One of the solutions to this problem is the creation of a platform that will unite all sports activities in the region. To quickly search for events, a recommendation system has been implemented that based on history will select sports events, which may be interested for the user. The system also allows users to create their own sport events in order to findparticipants. Based on the registration of users for sports events, the system will create statistics of the popularity of various sports among the population in the region.
Keywords: спортивні заходи; регіональна інформаційна система; управління подіями; спортивний менеджмент